DECENTRALIZATION OF PUBLIC ADMINISTRATION AS THE BASIS OF PUBLIC MANAGEMENT AT THE LOCAL LEVEL - Ladonko L.S.; Mykhailovska O.V.; Kundenko A.V. (Pressing Problems of Public Administration, 2016)
The article studies the characteristics of decentralization of public administration in Ukraine as apart of public management on the example of Chernihiv region. The effective forms of cooperationbetween public bodies of public administration at the local level are considered.